RESOURCE AVAILABILITY AND FIRM'S INTERNATIONAL STRATEGY AS KEY DETERMINANTS OF ENTRY MODE CHOICE - Tulung, Joy Elly (Universitas Brawijaya, Indonesia, 2017)
This study aimed to focus on the relationship between two main MNE's strategies that were multi-domestic and global. The choice of entry that examined not only the basis of Transaction Cost and Resource Based View but also incorporates a concept of Integration and Adaptation Cost. Moreover, the study includes an analysis brownfield investment and presents it as an alternative investment model in transition/emerging economies. This study examined by multi-domestic and the global strategy that were majority MNEs. Companies following a multi-domestic strategy will mostly depend on local firm's resources, such as local technology, local brand name, networking, and distribution channels. Their main purpose is to respond to the local market demands, which can best be achieved by the local subsidiaries of well-integrated. This study was a purely conceptual literature review, which is based on a substantial number of scientific and conceptual articles. This study decided to concentrate on the relationship between the resources, strategies and entry modes (including brownfield investment) because this study discovered a large research/literature gap in this field that very exciting.